Det radiologiske fund hos moseliget fra Grauballe - Krebs, Ratjen, Carl, Erling (Kuml, 1956)
The Radiological Examination of the Peat-bog Body from Grauballe In the spring of 1952, at the request of the Forhistorisk Museum, the X-Ray Department of the Aarhus Kommune-Hospital undertook a radiological examination of the Grauballe Man. The object of the examination was to determine to what extent there were signs of the use of violence, whether it was possible to decide more closely the man’s age, and finally whether his bones showed signs of any bone-disease. After commenting on certain technical difficulties arising from the waterlogged state of the body and the necessity of keeping it undisturbed, the authors give a detailed and step-bystep account of their results, ending with the following conclusion: X-Ray investigation gives grounds for believing that the subject is the body of an individual (male), undoubtedly about or above the age of 30 years. The results of a skull wound were discovered. This is situated in the region of the right forehead and temple. The wound appears to have been caused by a blunt instrument, as there is both a depression and a break-line. In addition an oblique fracture of the left shin-bone (tibia) was determined, but not of the fibula. Such a single fracture of one of the two bones of the lower leg suggests a direct blow, and is unlikely to have been caused by a fall. There are signs of a commencing rheumatism of the joints (spondylosis deformans) in the spinal column in the breast region, a disease which is rarely found in patients below the age of 30. All the other pathological details noted above can be naturally explained either as the results of a very long sojourn in a peat-bog or as the consequence of pressure from the overlying peat. Carl Krebs and Erling Ratjen